Automatic Health Care Unit - Zulqarnain; Ashraf, Obaid; Alia, Malka (International Journal of Endorsing Health Science Research, 2015)
This paper reflects on a novel concept of automation in the health care sector. The idea is to design an automatic system (AHCU) capable of performing remote physical examination with blood glucose estimation, pulse rate measurement, body mass measurement and body temperature measurement. The medical automatic system is consisted of a built-in dispenser to provide front-desk medicines to patient and also prescription in hard copy as well as in soft copy. In the Karachi city, we conducted first focus groups with doctors in order to identify how the remote medical diagnostician system is assessed and conceptualized regarding the examination procedures (activities), communication issues, and the visualization of needed information. The AHCU was found to be very reliable and efficient machine to provide front-desk monitoring, prescription and medication. It takes approximately 20 seconds to examine glucose level in blood, 10 seconds for fever measurement, 5 seconds in pulse rate measurement and 7 seconds for weight measuring. For providing medicines, it takes maximum 60 seconds in all cases. Based on the findings, we has reflected on the technology assessment, i.e., if remote medical services can be a suitable possibility for rural areas where the availability of doctors with various specializations is often a problem, as well as necessities for this novel type of medical treatment from a doctor's point of view (i.e., identified aspects increasing acceptance and adoption by users of the system).